2021
DOI: 10.1002/agt2.41
|View full text |Cite
|
Sign up to set email alerts
|

AIEgen‐enhanced protein imaging: Probe design and sensing mechanisms

Abstract: Proteins are the building blocks of life, regarded as one of the most complex and crucial biomacromolecules in biological systems, and playing a significant role in executing genes and transferring genetic information. According to recent research, due to the structural intricacy of proteins and their sensitivity to physical and chemical degradation processes, they could be utilized as biomarkers or therapeutic agents in the diagnosis, treatment, or even prevention of different diseases. Therefore, modern path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…S7, ESI †), and the twisting of the cyano group around the double bond indicated that the excitedstate fluorescent molecules could release energy through a nonradiative (CI pathway), which is similar to the previously reported AIE molecule. [48][49][50][51] Later, HR-MS analyses were further performed to clarify the activation mechanism. It was proposed that the TCFIS core was released upon addition of AChE enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…S7, ESI †), and the twisting of the cyano group around the double bond indicated that the excitedstate fluorescent molecules could release energy through a nonradiative (CI pathway), which is similar to the previously reported AIE molecule. [48][49][50][51] Later, HR-MS analyses were further performed to clarify the activation mechanism. It was proposed that the TCFIS core was released upon addition of AChE enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…[52,[55][56][57][58] Tetraphenylethylene (TPE) is a typical AIE luminogen. [59] With TPE unit introduced in the polymer backbones, P13(1a/2a/3a) (Scheme 4A) exhibited typical aggregation induced emission (Figure 1B). [4] It showed faint emission in its good solvent tetrahydrofuran (THF), however with the gradual addition of poor solvent water, its fluorescence intensity increased significantly, maximally reaching 17 times higher than that in its THF solutions at 90% of water fraction (f w ) (Figure 1C).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…In contrast to the usual fluorophores notion of aggregation-caused quenching (ACQ), the fluorescent emission of an organic fluorogen would be quenched in solid-state or aggregated form [ 18 , 19 ]. Strong emission, even at very low concentrations in the solid-state, demonstrates powerful and real-time monitoring potential in both in vitro and in vivo systems [ 20 , 21 , 22 ]. Due to the trend of utilizing various types of polymers in vitro trials or even in approved medical procedures, early studies have been implemented to monitor different aspects of AIE polymers in biosystems [ 23 ].…”
Section: Introductionmentioning
confidence: 99%